Determinants and role of farmers’ seed and seedling multiplication in the SNNP Region seed system - Walelign, G. (Haramaya University, 2008)
Increasing the production and productivity of the crop sub sector is one of the measures taken in Ethiopia to assure food security of more than 70 million people and escape from long-lived poverty persisted in the country. This improvement can only be realized if modern technologies are utilized from which seed take the first priority due to its nature. However, the low capacity of Government Company, sluggish growth of the private sector in the seed industry and the nature of the demand of subsistent farmers obliged to seek for another alternative seed source. Farmers’ based seed multiplication is the main alternative. Even though farmers’ based seed multiplication contributes to livelihood of farmers besides improving seed supply like any other technology, the participation of farmers in the multiplication is constrained by different farm characteristics, socio-economic and institutional factors. Hence to evaluate the contribution and identify most influencing factors of farmers based seed multiplication in SNNP region four types of seed multiplication (coffee, wheat, apple and potato)were considered for the fact that farmers commonly multiply in their respective Woredas in the region (Dale, Angacha, Chencha and Hula Woredas). Primary and secondary data were employed in this research mainly primary data were used from interview result of 60 randomly selected farmers from 2Kebeles of each indicated Woreda and totally 240 sample farmers. In order to describe and compare different categories of the sample units with respect to the desired characteristics, mean, standard deviation and percentage were computed. Further more t-test and chi-square test were used to supplement or testify significance of results obtained. A Tobit model was employed to identify the determinants variable to farmers’ involvement in seed multiplication activity and intensity of multiplication. In order to analyze the contribution of involvement in seed/seedling multiplication and evaluate the performance of seed market in the region gross margin analysis and Gross Marketing Margin analysis were employed besides qualitative description of the situation.